Low-energy electron inelastic mean free paths for liquid water. (21st March 2018) - Nguyen-Truong, Hieu T
Abstract: We improve the Mermin–Penn algorithm (MPA) for determining the energy loss function (ELF) within the dielectric formalism. The present algorithm is applicable not only to real metals, but also to materials that have an energy gap in the excitation spectrum. Applying the improved MPA to liquid water, we show that the present algorithm is able to address the ELF overestimation at the energy gap, and the calculated results are in good agreement with experimental data.